Sector-Level Productivity, Structural Change, and Rebalancing in China - Nabar, Malhar (IMF Working Papers; Working Paper ;, 2013)
This paper studies structural changes underlying China's remarkable and unprecedented growth in recent years. While patterns of structural transformation across China's provinces are broadly in line with international experience, one important difference is in labor productivity differentials between services and the rest of the economy. Specifically, the gap between labor productivity in the rest of the economy and services has widened across China's provinces as they have moved from low to middle income, which is contrary to the trend observed in cross-country experience. Evidence from a panel of China's provinces suggests that credit and labor market frictions have inhibited labor productivity growth in services relatively more than in the rest of the economy. Reducing these frictions is essential for achieving the next stage of China's development, one in which the service sector will need to play a more prominent role as an engine of growth. The evidence also suggests that improving labor productivity in services will lift the consumption share of GDP, thereby advancing the needed rebalancing of domestic demand in China.